Burundi : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report, 2011)
Burundi's extreme poverty, post-conflict environment, and persistent fragility created considerable risks to program implementation, calling for extensive flexibility in engagement. The program succeeded in establishing some of the key foundations of macroeconomic stability, mobilizing donor resources, and promoting poverty reduction. A successor program should strike the right balance between reforms narrowly aimed at improving the conduct of macroeconomic policies and other macro-critical reforms. Ensuring public debt sustainability should remain a key program objective. Risks to the new program are likely to remain high but manageable.